THE EXISTENCE OF ISLAMIC SHARIA AND SECURITY AS THE EFFORT FOR INVESTMENT INCREASING IN ACEH PROVINCE - Malahayatie; Ali Muhayatsyah (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2021)
The Research tries to identify the existence factor of Islamic sharia also the security issue that still constrain the invesment because Aceh as the area with conflict history of long term conflict. The existence of security factor for investor is the most important variable in investment climate because the investors expect that the security guarantee for investment sustainability in an area. Islamic Syari’ah is supposed as one of factor that Aceh goverment policy in its implementation faced many problems itself so that, it will become an obstacle in investment.Islamic Syari’ah not become as all the contrainst or obstacle in investment. The initial and fisrt objective from Islamic syari’ah implementation is to implement and realize the benefit of people in community and it was implemented in Maqashid Asy-Syariah. Related with the investment that tightly related with maqashid Hifzul Al-Maal Principles (secure and keep the property well). Islamic Syari’ah Existence is the sequence of security existence as the manifestation from benefit of the soul maintenence and care. Maqashid Asy-Syariah become benchmark in Islamic syari’ah implementation in Aceh could be applied and implemented in many policies program in all aspect especially in economy. By paying attention to the benefit of the security factor in Aceh, it will be created by itself because security and peace in muamalah is the goal of Islamic Sharia itself.